(untitled) (Malaysian Journal of Learning and Instruction, 2021)
Purpose – Given the prevalence of mental health issues among young adolescents and its detrimental effects on academic functioning, Social- Emotional Learning (SEL) interventions are becoming extremely valuable. The current study aims to investigate the effectiveness of two types of SEL interventions delivered by two different types of teachers to determine their effectiveness for SEL knowledge, learning anxiety, and intention to drop-out. Methodology – This study employed a 2 x 2 factorial and between-subject quasi-experimental design, in which intervention type and teacher type were manipulated to produce four different versions of experiments. A total of 209 students (107 boys, 102 girls) from Grade 8 with a mean age of 14.3 years from Qinzhou City in Southwest China participated in the study. Findings – Factorial and between-group MANOVA revealed that while psychology teacher was more effective in enhancing SEL knowledge and reducing dropout intention, regular teacher was more effective in reducing learning anxiety. TASSEL intervention was more effective in enhancing SEL knowledge while SEL regular intervention was more effective in reducing learning anxiety. Nevertheless, within-group analysis suggested TASSEL with psychology teacher was the best combination in reducing dropout intention while SEL with psychological teacher was the best combination in reducing learning anxiety. Significance – The results have significance for schools and mental health counselling services. The findings can guide the effective design of SEL intervention and appropriate teachers to deliver it.